2020
DOI: 10.15611/aoe.2020.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Is reputational risk important for bank performance? Evidence from CEE-11 countries

Abstract: The 2007-2009 revealed the weaknesses of the growth foundation and failure of risk management systems in large global banks. Consequently, there has been renewed interest in the creation of stable and functional risk culture. Protecting a financial institution’s reputation is among the most significant challenges facing financial firms. Thus the aim of this paper is to analyze why reputational risk is important for banks, and to trace its sources and consequences. In the empirical part, the paper proposes a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The measurement of reputational risks is the least studied research issue with 5 articles. This is consistent with the difficulty with measuring reputational risks (Gatzert et al, 2016;Miklaszewska et al, 2020); although, awareness has increased considerably, relative to other risks (Heidinger & Gatzert, 2018). The review identified two strands of literature on the measurement of reputational risks in banks.…”
Section: Research Issuessupporting
confidence: 58%
See 4 more Smart Citations
“…The measurement of reputational risks is the least studied research issue with 5 articles. This is consistent with the difficulty with measuring reputational risks (Gatzert et al, 2016;Miklaszewska et al, 2020); although, awareness has increased considerably, relative to other risks (Heidinger & Gatzert, 2018). The review identified two strands of literature on the measurement of reputational risks in banks.…”
Section: Research Issuessupporting
confidence: 58%
“…Strategy related mitigation factors include, identification of broader stakeholder expectations, aligning strategy with higher order goals (Tăchiciu et al, 2020), inter alia. Management related mitigation factors involves the preparation of an organization to deliver on its commitments (Miklaszewska et al, 2020), increasing reputational risks awareness (Trostianska & Semencha, 2019), inter alia. Governance related mitigation factors include transparency in environmental, social and governance policies, effective reputational monitoring system, adoption and implementation of the Equator principles (Mason & Ying, 2020;Banhalmi-Zakar, 2016;Eisenbach et al, 2014), standard model for the reporting of non-financial results, remuneration policies, and self-regulation (Saleuddin, 2014), inter alia.…”
Section: Research Issuesmentioning
confidence: 99%
See 3 more Smart Citations